2012
DOI: 10.1186/1471-230x-12-14
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the aspartate aminotransferase-to-platelet ratio index for the prediction of hepatitis B-related fibrosis: a leading meta-analysis

Abstract: BackgroundThe aspartate aminotransferase-to-platelet ratio index (APRI), a tool with limited expense and widespread availability, is a promising noninvasive alternative to liver biopsy for detecting hepatic fibrosis. The objective of this study was to systematically review the performance of the APRI in predicting significant fibrosis and cirrhosis in hepatitis B-related fibrosis.MethodsAreas under summary receiver operating characteristic curves (AUROC), sensitivity and specificity were used to examine the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
102
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 35 publications
11
102
1
5
Order By: Relevance
“…The second scale detects clinically significant fibrosis (Ishak stage 3-6); an APRI score >1.5 is the cut-off for significant fibrosis, whereas a score <0.5 can rule it out (45). In a meta-analysis published in 2012 (46), which included nine studies (n=1,798), the APRI gave AUROCs for significant fibrosis and cirrhosis of 0.79 and 0.75, respectively. For significant fibrosis, an APRI cut-off of 0.5 had a sensitivity of 84% and a specificity of 41%, while a cut-off of 1.5 had a sensitivity of 49% and a specificity of 84%; for cirrhosis a cut-off range of 1.0-1.5 had sensitivity and specificity of 54% and 78% respectively and a cut-off of 2 28% and 87% respectively, leading the authors to conclude that the APRI had limited application in the identification of significant fibrosis or cirrhosis in HBV.…”
Section: Aprimentioning
confidence: 99%
“…The second scale detects clinically significant fibrosis (Ishak stage 3-6); an APRI score >1.5 is the cut-off for significant fibrosis, whereas a score <0.5 can rule it out (45). In a meta-analysis published in 2012 (46), which included nine studies (n=1,798), the APRI gave AUROCs for significant fibrosis and cirrhosis of 0.79 and 0.75, respectively. For significant fibrosis, an APRI cut-off of 0.5 had a sensitivity of 84% and a specificity of 41%, while a cut-off of 1.5 had a sensitivity of 49% and a specificity of 84%; for cirrhosis a cut-off range of 1.0-1.5 had sensitivity and specificity of 54% and 78% respectively and a cut-off of 2 28% and 87% respectively, leading the authors to conclude that the APRI had limited application in the identification of significant fibrosis or cirrhosis in HBV.…”
Section: Aprimentioning
confidence: 99%
“…32,33 In this study, 164 chronic hepatitis B patients underwent liver biopsies before treatment. Liver fibrosis in patients with RT mutations was more severe than in patients without RT mutations, and liver fibrosis in patients with multiple mutant sites (≥2) was more severe than in patients with a single mutant site.…”
Section: Discussionmentioning
confidence: 99%
“…It was used in several studies conducted in cohorts of patients with hepatitis C and showed a rather good diagnostic performance and reproducibility, [110] particularly for cirrhosis. Forns and colleagues reported a fibrosis index (Forns' index) based on platelet count, γ-glutamyl transferase (GGT), and cholesterol levels [111].…”
Section: Non-invasive Tests For Liver Disease and Assessment Of Fibromentioning
confidence: 99%